Entrepreneurial Self-Efficacy, Passion, and Opportunity Recognition in Garut's Millennial Coffee Entrepreneurs - Helni, Helni; Hamdani, Nizar Alam; Maulani, Galih Abdul Fatah (Entrepreneurship Faculty, Universitas Garut, 2025)
The background of this research is the use of Opportunity Recognition which is still lacking, especially in the millennial generation in Garut Regency. The low level of ability to recognize business opportunities hinders economic growth, innovation and business development. The aim of this research is to analyze the influence between entrepreneurial self-efficacy and entrepreneurial passion on opportunity recognition in millennial generation entrepreneurs (survey of coffee MSMEs in Garut Regency). This type of research is survey research with a quantitative approach. The sample used was 75 respondents who were distributed using a questionnaire via Google Form media and then processed using SmartPls 4.0 software using simple random sampling. The analysis used in this study is the R-Square value, as well as hypothesis testing using the bootstrap method and T statistics. The results of this research show that there is a significant influence between Entrepreneurial Self-Efficacy on Opportunity Recognition in millennial entrepreneurs, with an original sample value of 0.290. The research results also show that there is a significant influence between Entrepreneurial Passion on Opportunity Recognition in millennial entrepreneurs, with an original sample value of 0.512. The Opportunity Recognition variable has a significant influence of 0.536 or 53.6% on Entrepreneurial Self-Efficacy and Entrepreneurial Passion and the other 46.4% is influenced by variables not mentioned in this research model.